(untitled) (Journal of Economic Research & Business Administration, 2018)
The importance of studying the current problems of the labor market is due to the fact that the proclaimed course of the third modernization of Kazakhstan involves ensuring dynamic growth of the economy based on its accelerated technological modernization and, accordingly, the creation of a fully functioning labor market. Until now, the essence and content of the modernization of the labor market and the influence of various factors on the dynamics of its development are not fully reflected in domestic science. Particularly, there is the question of the degree of state intervention in the processes of labor market regulation. In the new conditions, the modernized labor market, in turn, should become a factor of economic growth. In this regard, it is advisable to critically rethink the methods of analyzing and forecasting labor supply and labor demand, mechanisms for the formation of wages and the functioning of labor market institutions and other issues that characterize the current state of the labor market in the country. The situation on the labor market in Kazakhstan is largely determined by the imbalance of labor supply and demand for labor. In this regard, it is important to determine the factors determining the relationship between them. This article deals with the problems of labor supply formation (CP) in the Kazakhstan labor market under the influence of various factors. Their study is important both in theoretical and in practical terms. Numerous studies of the labor market focus on two main macroeconomic indicators — GDP and unemployment (employment), and unfairly little space is devoted to studying the supply of labor. Meanwhile, it is the quantitative and qualitative characteristics of the ORS and their comparison with the demand for labor determine the direction and content of measures to achieve a balance between them. Methodology of research. The methodological basis of the problems discussed in the article are the studies of foreign and domestic scientists on this problem. Due to the impossibility of covering the entire set of complex labor market issues, this article focuses on the study of the problem of forecasting labor supply in the labor market in Kazakhstan. Based on the general laws governing the functioning of the labor market, the volume of labor supply is analyzed and projected depending on the influence of various factors that reflect the specific conditions of economic development and the particularities of the Kazakhstani model of the labor market. On the basis of a comparative analysis of the use of a number of techniques, a specific method for predicting an ORS was proposed, the approbation of which on materials from Kazakhstan confirmed the high accuracy of the forecast of the indicator under consideration. Our analysis was carried out on the basis of statistical data of the Committee on Statistics of the Ministry of National Economy of the Republic of Kazakhstan, reflecting the development of the country’s economy for 2005-2016. The choice of this period of time from a methodological position is also not accidental, it was during this period that the country’s economy experienced two crises with an interval of 6-8 years, which in principle is characteristic of a market economy. At the same time, the problem of searching for a new model of economic growth was clearly revealed. Accelerated technological modernization of the economy is recognized as the main priority in the implementation of the third modernization of Kazakhstan, which implies the mobilization of other opportunities, including the modernization of the labor market. In order for the modernized labor market to really become a factor of dynamic growth of the economy, it is necessary to achieve an accurate forecast of labor market indicators, in particular, the demand and supply of labor. This will reduce management costs, provide targeted social support to the unemployed and prevent social tensions in society.